Modern views on diabetes mellitus in individuals after cholecystectomy as a prerequisite for the substantiation and development of a physical rehabilitation program - Golod, Nataliya (Journal of Education, Health and Sport, 2017)
Actuality. Developing countries spend from 2.5 to 15.0 percent of their annual health care budgets on the treatment of diabetes mellitus (DM), and families with diabetes spend from 15 to 25 percent of their income on treatment. The growing diabetes pandemic is unfolding with a rapid increase in the prevalence of type 2 diabetes. Objectives of research. Determine the prevalence of diabetes mellitus. Analyze the impact of diabetes in terms of the rehabilitation prognosis of patients after cholecystectomy (CC). To determine the main strategies of physical rehabilitation to improve the quality of life of people with diabetes after cholecystectomy. Results of research. The prevalence of gallstone disease (GD) is significantly higher among people with diabetes (24.8%) than in the general population (13.8%), the physical and social consequences of which can have a negative impact on quality of life. During the initial assessment of people after CC for the purpose of developing a physical rehabilitation program, it is necessary to establish the presence of signs of prediabetes or DM, taking into account glucose and insulin resistance, as well as signs, symptoms and factors that may further contribute to the development of DM. When developing a physical rehabilitation program, the complications that this disease leads to should be taken into account. Rehabilitation interventions for such individuals should be based on evidence-based practice in the field of health care. Conclusions. The physical rehabilitation (PR) program should last at least 3 to 6 months, aimed at increasing physical activity (PA) (at least 150 minutes and 3 sessions per week of combined aerobic and strength training), normalizing body weight; for older people, the PR program should include measures to prevent falls and sarcopenia. Anxiety and depression levels need to be monitored. Conduct special training to encourage a healthy lifestyle, nutrition, reduced calorie intake, regular physical activity, sleep management, and reduction of anxiety and depression.